1998
DOI: 10.1046/j.1471-4159.1998.71010196.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Induces Apoptosis in Cerebellar Granule Neurons by Inhibiting Insulin‐Like Growth Factor 1 Signaling

Abstract: The ability of ethanol to interfere with insulinlike growth factor 1 (IGF-1 )-mediated cell survival was examined in primary cultured cerebellar granule neurons. Cells underwent apoptosis when switched from medium containing 25 mM Kto one containing 5 mM K~. IGF-1 protected granule neurons from apoptosis in medium containing 5 mM K~.Ethanol inhibited IGF-1-mediated neuronal survival but did not inhibit IGF-1 receptor binding or the neurotrophic action of elevated K~,and failed to potentiate cell death in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 33 publications
2
87
0
Order By: Relevance
“…Ethanol impairs neuronal growth and viability in the developing CNS by inhibiting growth factor-stimulated signaling mechanisms (9,11,13,18,51). Previous in vitro studies showed that ethanol inhibition of insulin-stimulated cell growth and viability were mediated by reduced activation of mitogen-activated protein kinase (42,43) and PI3 kinase (11,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanol impairs neuronal growth and viability in the developing CNS by inhibiting growth factor-stimulated signaling mechanisms (9,11,13,18,51). Previous in vitro studies showed that ethanol inhibition of insulin-stimulated cell growth and viability were mediated by reduced activation of mitogen-activated protein kinase (42,43) and PI3 kinase (11,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments demonstrated that neuronal loss following ethanol exposure was mediated by apoptosis (8 -10) or mitochondrial dysfunction (10 -12), and recent studies correlated these adverse effects of ethanol to inhibition of growth factor-stimulated survival signaling (9,(11)(12)(13). In the developing CNS, insulin and insulin-like growth factor type 1 (IGF-1) 1 receptors are abundantly expressed (14 -16), and the corresponding growth factor-stimulated responses are critical mediators of neuronal growth, viability, energy metabolism, and synapse formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophic factors can protect cells from programmed death (Cui et al, 1997;Luo et al, 1997;Zhang et al, 1998;Ikonomidou et al, 1999). There is evidence that some neurotrophic factors activate AP-1 and/or NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…Rat cerebellar granule neurons were prepared from 7-day-old rat pups as reported previously (42,43). Briefly, cerebella were obtained from postnatal day 7 Harlan Sprague-Dawley rat pups, cross-chopped (400 ϫ 400 M), and then treated with 0.025% trypsin-EDTA (including 0.01% DNase I) for 15 min, 37°C.…”
Section: Methodsmentioning
confidence: 99%